Acerca de la "Fiebre Grave de Carrión" - Hercelles, Oswaldo (1926)
The starting point of this work have been several cases of "fever of Carrion" in which a therapeutic purpose have made blood culture and with it, a vaccine that has been healing without the warty eruption occurs (have tried lately sick in Villar Clinic in July, with a surprising result.